2013
DOI: 10.1007/s10035-013-0430-z
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of weakly wetted granular materials: a comparison of experimental and numerical data

Abstract: Shear cell simulations and experiments of weakly wetted particles (a few volume percent liquid binders) are compared, with the goal to understand their flow rheology. Application examples are cores for metal casting by core shooting made of sand and liquid binding materials.The experiments are carried out with a Couettelike rotating viscometer. The weakly wetted granular materials are made of quartz sand and small amounts of Newtonian liquids. For comparison, experiments on dry sand are also performed with a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Earlier studies on wet granular materials have shown that the presence of liquid bridges between the particles results in an increasing steady-state cohesion of the materials [12,13,15,27]. Our earlier studies show that the steady-state cohesion c * increases non-linearly with increasing liquid bridge volume.…”
Section: Steady-state Cohesion and Its Correlation With Liquid Bridgementioning
confidence: 94%
See 3 more Smart Citations
“…Earlier studies on wet granular materials have shown that the presence of liquid bridges between the particles results in an increasing steady-state cohesion of the materials [12,13,15,27]. Our earlier studies show that the steady-state cohesion c * increases non-linearly with increasing liquid bridge volume.…”
Section: Steady-state Cohesion and Its Correlation With Liquid Bridgementioning
confidence: 94%
“…This model equation is applicable for mono-disperse particles [12,19], which has been actually extended to poly-disperse system of particles Ref. [14].…”
Section: Liquid Bridge Capillary Force Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only a few attempts have been made to answer this question, concerning dense metallic glasses [27,28], adhesive emulsions [29,30], attractive colloids [31][32][33], cemented granular media [34], wet granular media [35,36] and clayey soils [37]. Recently, rheological studies on adhesive emulsions and colloids [29][30][31]33] reported that the presence of attractive forces at contact affects shear banding by affecting flow heterogeneity and wall slip.…”
Section: Introductionmentioning
confidence: 99%